A privatizált vagyon visszaállamosítása Magyarországon 2010 - 2014 - Péter Mihályi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
– This study is a natural continuation of the author's earlier book on privatization in Hungary, covering the developments between 1989 and 2009 on 1700 pages. As it is well-known, the right wing FIDESZ government, which came to power with a 2/3 supermajority in Parliament, has embarked upon a totally new economic policy as from mid-2010. Within this setting, illiberal constitutional changes and unortodox economic policies were implemented. Renationalization was a significant (but not the most important) building block of this. As we analysed the individual transactions, it turned out that actually many of them were initiated by the previous, Socialist led government. In other words, there are interesting elements of continuity here, especially in the energy sector. Another interesting finding is, that almost without exceptions, the renationalization deals were not implemented by force, the Hungarian state paid quite generously to the sellers. In the case of the largest deals, there is even reason to speak of sweetheart deals through which the Hungarian government tried to make favour to German and US businesses. So far, the renationalization affected more than 200 firms (including banks) for which some HUF 1600 bn (≈ 5bn exteuro) state money was used. This figure, just as the sums involved in the individual transactions are somewhat misleading, if compared to the privatization revenues generated by previous governments prior to 2010. However, if all transactions – i.e. asset sales and asset purchases – are expressed as a percentage of Hungary's annual GDP, it becomes clear that the post 2010 nationalization deals were much smaller than the 1990-2000 privatization deals.
Keywords: P20; P26; P31; P51; 330; Nationalization; privatization; state ownership; illiberal economic policies